2016
DOI: 10.1371/journal.pone.0165562
|View full text |Cite
|
Sign up to set email alerts
|

Complex within a Complex: Integrative Taxonomy Reveals Hidden Diversity in Cicadetta brevipennis (Hemiptera: Cicadidae) and Unexpected Relationships with a Song Divergent Relative

Abstract: Multiple sources of data in combination are essential for species delimitation and classification of difficult taxonomic groups. Here we investigate a cicada taxon with unusual cryptic diversity and we attempt to resolve seemingly contradictory data sets. Cicada songs act as species-specific premating barriers and have been used extensively to reveal hidden taxonomic diversity in morphologically similar species. The Palaearctic Cicadetta montana species complex is an excellent example where distinct song patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 73 publications
2
17
0
3
Order By: Relevance
“…Use of the subspecies classification for Neotibicen similaris apalachicola is consistent with the approach applied to cicadas in the genera Pauropsalta Goding & Froggatt (Popple 2013), Cicadetta Kolenati (Hertach et al 2016) and Thopha Amyot & Audinet-Serville , although the song differences are greater in our case. In those cases, as here, the described taxa exhibit low levels of genetic and morphological divergence and have geographic relationships ranging from allopatric to parapatric with hybridization.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Use of the subspecies classification for Neotibicen similaris apalachicola is consistent with the approach applied to cicadas in the genera Pauropsalta Goding & Froggatt (Popple 2013), Cicadetta Kolenati (Hertach et al 2016) and Thopha Amyot & Audinet-Serville , although the song differences are greater in our case. In those cases, as here, the described taxa exhibit low levels of genetic and morphological divergence and have geographic relationships ranging from allopatric to parapatric with hybridization.…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies have revealed additional complexes of parapatric cicada species and/or subspecies that hybridize in apparent zones of secondary contact (Hertach et al 2016;Marshall et al 2011;Popple 2013). The case presented here is remarkable in that Neotibicen similaris apalachicola is almost surrounded by populations of N. similaris similaris, so it is possible that the latter contains cryptic lineages from different climatic refugia (one on either side of N. similaris apalachicola).…”
Section: Discussionmentioning
confidence: 71%
“…Cicadas are hemipteran insects known for their multiple-year life cycles, some of which are the longest known in non-eusocial insects, and for their loud, complex, and usually species-specific acoustic sexual signals or songs (Myers 1929;Claridge 1985;Williams & Simon 1995). Cicadas have become useful model organisms for studies of speciation and biogeography, because songs allow rapid assessment of local cicada communities and facilitate the detection of cryptic taxa at early stages of divergence (Marshall et al 2011;Hertach et al 2016). Cicadas have also become a focus of studies of endothermy (e.g., Sanborn et al 2003;, of endosymbiosis, where extraordinary examples of genome evolution have been documented (McCutcheon et al 2009;Van Leuven et al 2014;Campbell et al 2015), and in technology where the nanostructure of cicada wings has served as a template for nanolithography to create hydrophobic, antireflective and/or antibiotic surfaces (Zhang et al 2006;Xie et al 2008;Hasan et al 2013;Zada et al 2016;Lin et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…General distribution (only acoustically-validated data): Southern Europe : Bulgaria, Croatia, Italy, Romania, Serbia, Slovenia; Central Europe : Austria, Hungary (summarised by Hertach et al 2016 ).…”
Section: Checklistsmentioning
confidence: 99%